2023
DOI: 10.3390/bioengineering10030291
|View full text |Cite
|
Sign up to set email alerts
|

Long-Bone-Regeneration Process in a Sheep Animal Model, Using Hydroxyapatite Ceramics Prepared by Tape-Casting Method

Abstract: This study was designed to investigate the effects of hydroxyapatite (HA) ceramic implants (HA cylinders, perforated HA plates, and nonperforated HA plates) on the healing of bone defects, addressing biocompatibility, biodegradability, osteoconductivity, osteoinductivity, and osteointegration with the surrounding bone tissue. The HA ceramic implants were prepared using the tape-casting method, which allows for shape variation in samples after packing HA paste into 3D-printed plastic forms. In vitro, the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Kresakova et al [ 16 ] have demonstrated HA implants in 12 female sheep with critical size defects in the load-bearing bone. During 6 months of follow-up, there was were no clinical signs of infection, inflammation, or pathological wound damage.…”
Section: Bioceramics In Hard Tissue Regenerationmentioning
confidence: 99%
“…Kresakova et al [ 16 ] have demonstrated HA implants in 12 female sheep with critical size defects in the load-bearing bone. During 6 months of follow-up, there was were no clinical signs of infection, inflammation, or pathological wound damage.…”
Section: Bioceramics In Hard Tissue Regenerationmentioning
confidence: 99%
“…[6,7]. Hydroxyapatite (HAP) and other ceramics have been repeatedly tested in animals for the treatment of bone defects [8][9][10][11][12]. Recently, attention has been paid to the use of calciumphosphate-fluorine ceramics (fluorapatite or fluorhydroxyapatite) in medicine; however, this material has not been tested in vivo for stimulation of bone defect healing.…”
Section: Introductionmentioning
confidence: 99%